Management of Femoral Shaft Fractures in Children with Skeletal Traction Followed by Hip Spica Cast Versus Flexible Intramedullary Nailing (Journal of Pakistan Orthopaedic Association, 2014)
Background: The treatment of femoral shaft fractures has always been a focus of interest especially in children, but may still remain a clinical problem and a subject of controversy.Objective: To compare the post-operative outcomes of hip spica and flexible intramedullary nails in treatment of femoral shaft fractures in children. Material &Methods: Randomized controlled trial conducted for six months at Department of Orthopaedics Bahawal Victoria Hospital Bahawalpur. A total of 112 children, 6–12 years old, with simple femoral-shaft fractures were randomized to receive skeletal traction followed by hip spica cast (n = 56) or FIN (n = 56). Length of hospital stay, time to start independent walking, and range of knee motion were compared between the two groups 4 months after injury.Results: The two groups were similar in background characteristics. Compared with the children treated with spica cast, those treated with FIN achieved their recovery milestones much earlier. Children treated with FIN had shorter hospital stay (6.25+_2.41days) as compared to hip spica group (22.71+_3.17 days) and took a shorter time to start walking independently (37.23+_7.22) as compared to hip spica group (73.04+_10.24). Range of knee motion was 131.73 ± 5.2° in the spica cast group and 135.84 ± 5.39° in the FIN group at the end of 4 months. Complication rate was much less with FIN and overall patients and parents satisfaction rate was higher.Conclusion: The results showed significant benefits for FIN compared with traction and hip spica cast and complication rates associated with hip spica cast was also higher than that associated with FIN.Keywords: Spica cast, flexible intramedullary nailing, Femoral-shaft fracture, Pediatrics.